Analysis of Inhibiting Factors in Electric Motor Conversion Learning in Vocational High School - Fitra Sayyoda; Hasan Maksum; Dony Novaliendry (Journal for Lesson and Learning Studies, 2025)
The rapid development of electric vehicles requires competent human resources; however, the implementation of electric motorcycle conversion learning in vocational schools faces challenges related to facilities, teacher competence, and industry support. This study aims to identify the inhibiting factors affecting its implementation in the Motorcycle Engineering Department of vocational high schools. The research method uses a qualitative descriptive approach. Research subjects included productive teachers, head of expertise concentration, and grade XI students who participated in electric motor conversion learning. Data collection techniques used observation, in-depth interviews, and documentation with observation guidelines and semi-structured interview guidelines as instruments. Data analysis used the Miles and Huberman model including data reduction, data display, and conclusion drawing. The research results identified five main factors inhibiting electric motor conversion learning, namely: limited facilities and infrastructure with only one conversion kit available for 200 students, limited teacher competence where only 2 of 5 teachers attended training, curriculum not explicitly integrated with electric vehicle learning, minimal industry partnerships, and limited budget allocation for electric vehicle learning development. In conclusion, the implementation of electric motorcycle conversion learning in vocational schools is hindered by five interrelated factors. A comprehensive strategy is required, including improved practical facilities, strengthened teacher competence, curriculum adjustment, industry partnerships, and optimized budget allocation to ensure sustainable and high-quality learning.